Aplicación de la digestión anaerobia para la producción de biogás a partir de aguas residuales en zonas no interconectadas de Colombia. (2022)
In this work, the application of anaerobic digestion is proposed, as a process for the use of agricultural wastewater and the generation of alternative energies such as biogas, in rural areas of Colombia, where there are no sewage systems and, therefore, Therefore, discharges are disposed of in water sources, forests, soils, etc. thus contaminating the ecosystem, not only affecting aquatic and plant life, but also human health, since according to Alférez and Nieves (2019) these contain large amounts of pathogenic microorganisms that generate multiple diseases. On the other hand, the rural areas to which this project can be applied are defined as non-interconnected areas (ZNI) where the public electricity service is not provided through the country's Interconnected System, taking advantage of biogas as electrical energy. First, a contextualization and consolidation of information on the production of biogas through the anaerobic digestion of agricultural wastewater is carried out, the description of this process, the types of biodigesters and microorganisms that can be used and how to take advantage of the biogas obtained for production. Of electricity. Taking into account the current legal framework for this type of activity. Also knowing the amount of manure that is produced annually in the country, whose organic matter can be used for the production of biogas.